Environmental Psychology in Latin America: Trends and invisibilities in mainstream scientific production - Mardones, Rodolfo Estaban; Berroeta, Héctor (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2024)
Environmental psychology is a field focused on understanding the relationships between individuals and the socio-physical environment. It has seen extensive development in the United States and Europe, with notable contributions from authors, institutions, and journals in the global north, leaving a gap in the development of environmental psychology in the global south. Consequently, our goal is to analyze the scientific production of Latin American environmental psychology. To achieve this, we examine a sample of scientific production from Latin America in publications indexed in the Web of Science and Scopus. To characterize the literature, we analyze socio-bibliometric aspects and conduct a thematic analysis of its content. Findings indicate that author collaboration is characterized by small and regionally unassociated groups. The trends in literature published on the Web of Science and Scopus reveal a predominantly traditional Environmental Psychology, both in methodologies and addressed themes. The discussion emphasizes the invisibility of relevant research and interventions to analyze the historically situated production of people and the socio-physical environment, as well as mechanisms maintaining social order.